Alberto Magno en Los Andes : la escultura de Gerhard Marcks - Marcks, Gerhard, 1889-1981 (Universidad de los Andes, Ediciones Uniandes, 2019)
'Albertus Magnus' is the best-known work of German sculptor Gerhard Marcks (Berlín, 1889 - Colonia, 1981). The bronze statue of saint Albert the Great located in the campus of the Universidad de los Andes and known as El Bobo' is one of the four replicas found in different parts of the world. "The book ... is a simple but important tribute that the University makes to this historic Uniandes symbol - as a sculpture, as a monument, as an emblem and as a badge - to remember its history, that of its author and that of the figure of Saint Albert Magnus. It is a modest contribution to the celebration of our 70 years of existence that we deliver to the Uniandes community so that we understand and appreciate more our beloved Bobo." (HKB Translation) --Verso Cover.